2019
DOI: 10.1158/0008-5472.can-18-0781
|View full text |Cite
|
Sign up to set email alerts
|

TLR Signaling Is Activated in Lymph Node–Resident CLL Cells and Is Only Partially Inhibited by Ibrutinib

Abstract: Chronic lymphocytic leukemia (CLL) is a malignancy of mature B cells driven by B-cell receptor (BCR) signaling and activated primarily in the lymph node. The Bruton's tyrosine kinase (BTK) inhibitor ibrutinib effectively inhibits BCR-dependent proliferation and survival signals and has emerged as a breakthrough therapy for CLL. However, complete remissions are uncommon and are achieved only after years of continuous therapy. We hypothesized that other signaling pathways that sustain CLL cell survival are only … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
67
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(73 citation statements)
references
References 56 publications
6
67
0
Order By: Relevance
“…At a concentration of 10 μmol/l, IRAK4i reduced cell viability in 41 out of 43 samples analysed while it had no or a protective effect in two samples (the percentage of cell viability for each CLL sample is reported in Table SI). These data suggested that CLL cells incubated in vitro might still partially depend on TLR signalling for their survival, likely reminiscent of previous microenvironmental interactions occurring in lymph nodes (Dadashian et al , ) strongly indicating the TLR signalling pathway as a novel druggable target in CLL. However, among the 41 ‘responsive’ cases (i.e.…”
Section: Resultsmentioning
confidence: 57%
See 4 more Smart Citations
“…At a concentration of 10 μmol/l, IRAK4i reduced cell viability in 41 out of 43 samples analysed while it had no or a protective effect in two samples (the percentage of cell viability for each CLL sample is reported in Table SI). These data suggested that CLL cells incubated in vitro might still partially depend on TLR signalling for their survival, likely reminiscent of previous microenvironmental interactions occurring in lymph nodes (Dadashian et al , ) strongly indicating the TLR signalling pathway as a novel druggable target in CLL. However, among the 41 ‘responsive’ cases (i.e.…”
Section: Resultsmentioning
confidence: 57%
“…As constitutive TLR signalling has been shown to be crucial for the survival of CLL cells even in the absence of this genetic drive, which is rarely observed in CLL, we reasoned that interfering with the TLR pathway may induce a potential therapeutic effect. Indeed, a recent paper showed that a dual IRAK1/4 inhibitor was able to block TLR stimulation in CLL cells (Dadashian et al , ). In addition, Gimenez et al () very recently reported that the IRAK4 inhibitor ND2158 disrupted inflammatory pathways and delayed tumour development in CLL.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations